Dissolved methane in anaerobic effluents: A review on sustainable strategies for optimization of energy recovery or internal process reuse. (1st October 2021) - Stazi, Valentina; Tomei, Maria Concetta
Abstract: The growing interest in public health and environmental protection, and the need of resource recovery imposed by the environmental sustainability, induce to look at the anaerobic wastewater treatment as an attractive alternative to the current aerobic treatment practice. In order to exploit the great potential of anaerobic wastewater treatment, thanks to the consolidated technology of high rate bioreactors, the presence in the treated effluent of dissolved CH4 deserves further investigation to avoid energy loss and to reduce greenhouse gas emissions. Reported concentrations of dissolved CH4 in anaerobic effluents can account for about half of the total production, thus strategies for its recovery as energy source, or reuse by biological oxidation within the same treatment line, are the keys to approach energy-neutral anaerobic treatment, and to valorize the intrinsic features of such process to be economically feasible and environmentally friendly. The aim of this review is to offer a complete overview of the available technologies, both for the dissolved CH4 recovery through physical methods, such as aeration, gas stripping and degassing membranes, and for its biological removal through down-flow hanging sponge reactors and the more recent proposed process based on denitrification and anaerobic CH4 oxidation (DAMO). Each technology has been deeply described highlighting weaknesses and strengths at different operating conditions and bioreactor configurations. The resulting critical analysis allowed identifying the knowledge gaps still existing in the field and the related research needs. Graphical abstract: Image 1 Highlights: Anaerobic treatment of wastewaters allows energy and resources recovery. Dissolved CH4 can cause energy loss and dangerous greenhouse gas emissions. Strengths and drawbacks of available technologies for dissolved CH4 recovery/reuse. Comparative analysis of CH4 management strategies to define future research needs.